Professional Development Program for Civil Servants for Creation a Safe Educational Environment under Martial Law - Iryna Trubavina; Oleksandr Cherednychenko; Kirill Nedria; Nadiia Oliinyk (Educational Challenges)
The relevance of the article is determined by the need to train education managers – civil servants and officials of local self-government bodies – to work and manage the educational system in war conditions.